Pelatihan Pemasaran Online Produk Jangek Uda Sap Rawa Makmur Kota Bengkulu dengan Menggunakan media Sosial Tiktok - Astuty, Kamelia; Kristina, Nevianti; Rahman, Abdul (Jurnal Dehasen Mengabdi, 2023)
This community service is carried out with the aim of enabling UdaSap MSME players to understand and practice online marketing of the jangek products they produce to increase household income. This online marketing training was attended by Uda Sap and his wife who were the perpetrators. Training is carried out by providing education and outreach about online marketing, especially through social media Tiktok, which is then continued with exploration and practice of online marketing through social media. The resulting output is that the training participant has a Tiktok account and starts with registering an account on Tiktok and entering the product to be sold. The marketing of Jangek Uda Sap products is still carried out conventionally due to limited knowledge about online marketing. However, through the training provided there is a development of understanding of the importance of online marketing. Apart from that, there is also a change in mindset regarding online marketing which is supported by the start of using TikTok shop accounts for marketing Jangek uda Sap crackers. It is hoped that with this training, Sap as an MSME actor can market his MSME products through social media and can increase sales.